Polyassociative thermodynamical model of A₂B₆ semiconductor melt and P-T-X equilibria in Cd-Hg-Te system: 1. Phase equilibria in initial two-component systems. Hg-Te system - Moskvin, P.P.; Rashkovets'kyi, L.V.; Kavertsev, S.V.; Zhovnir, G.I.; Ruden'kyi, A.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
In the framework of the theory for associated solutions comprising several complexes of various compositions in a liquid phase, analyzed are phase equilibria in Cd-Hg-Te systems. Checking this theory as to the description of phase equilibria in a system as well as a search of model thermodynamic parameters were performed by the way of sequential computer processing the respective experimental results for initial two-component materials. Hg-Te system was chosen as the first model one. It was ascertained that HgTe, HgTe₂ and Te are dominating complexes in the liquid phase of this system. Determined were the complex-creative parameters in the liquid phase. As to P-T-X equilibria in Hg-Te system, we reached a satisfying accordance between calculation and experimental data.